2020
DOI: 10.1136/bmjopen-2019-034934
|View full text |Cite
|
Sign up to set email alerts
|

Fast track rehabilitation after reversed total shoulder arthroplasty: a protocol for an international multicentre prospective cohort study

Abstract: IntroductionThe use of reversed total shoulder arthroplasty (rTSA) has increased because of an increasing number of indications for this procedure and by ageing of the population. Usual postoperative care consists of immobilisation of the shoulder for a period of 2–6 weeks to allow healing of the subscapularis tendon and protection of the joint. However, new literature proved that reattachment of the subscapularis tendon is unnecessary. Therefore we hypothesised that immobilisation of the shoulder is not neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Active and passive exercises of finger joints, elbow and wrist joints can be carried out two days after surgery to restore joint movement and reduce the occurrence probability of apraxia muscular atrophy and postoperative stiffness. [16,17] ROM score and ASES score are the main indexes to evaluate shoulder joint function after ARCR; The higher the ROM score and ASES score, the better the shoulder joint function. Hagen et al [5] found that joint ROM such as flexion, extension and abduction in the early rehabilitation group after shoulder joint replacement was significantly improved compared with that in the delayed rehabilitation group, avoiding local tissue spasm and joint stiffness after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Active and passive exercises of finger joints, elbow and wrist joints can be carried out two days after surgery to restore joint movement and reduce the occurrence probability of apraxia muscular atrophy and postoperative stiffness. [16,17] ROM score and ASES score are the main indexes to evaluate shoulder joint function after ARCR; The higher the ROM score and ASES score, the better the shoulder joint function. Hagen et al [5] found that joint ROM such as flexion, extension and abduction in the early rehabilitation group after shoulder joint replacement was significantly improved compared with that in the delayed rehabilitation group, avoiding local tissue spasm and joint stiffness after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There's consensus about early mobilization in elderly patients to decrease inconvenient and limitation due to use of sling [34]. A recent review of literature shows no consensus for postoperative rehabilitation protocol after RSA and publications concerning rehabilitation protocol avec RSA in traumatology are very rare [14,[35][36][37]. Both groups have very satisfactory clinical and functional results comparatively to literature [8,11,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation protocols are based on common principles but its differ regarding to several variables: postoperative delay, authorized movements, active/passive work, short and long term precautions which can explication for a part of complications [37,40,41]. Concerning complications, only one case of luxation was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Later FE strength recovery may also be explained by greater limitations on rehabilitation in the immediate weeks after aTSA in an effort to protect the subscapularis repair. 5 , 10 Furthermore, the reliance on a healing subscapularis for shoulder stability after aTSA may result in pain that limits strength, whereas stability in rTSA is dependent on the deltoid. 10 , 11 , 12 , 18 These differences in the biomechanics, postoperative rehabilitation, and stability likely also explain the early loss of both ER and FE strength between baseline and 3 months after aTSA but not after rTSA ( Figure 1 , Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%